Formation and Dispersal of Ash at Open Conduit Basaltic Volcanoes: Lessons From Etna - Edwards, Matthew J.; Eychenne, Julia; Pioli, Laura (Frontiers in Earth Science, 2021)
Open conduit volcanoes are characterized by frequent, small scale explosive eruptions, which have a significant impact. Ash-forming explosions are impacting over larger areas with respect to effusive or poorly explosive events and, consequently, are more significant for hazard assessments. Quantifying the hazard associated with them requires understanding the processes and parameters controlling explosive style, and tephra dispersal and obtaining a comprehensive dataset to constrain syn-eruptive dynamics and particle transport in the volcanic plume. We present a study focused on Etna volcano (Italy), which, despite its continuous outgassing through the summit vents, has very frequent explosive eruptions dispersing ash along the southern Mediterranean area. The goal of this study is to obtain a statistically valid dataset on ash morphology and texture and investigate how various particle types distribute spatially in the tephra blanket. We chose a small scale, ash-forming eruption occurred in May 2016, sampled a few hours after tephra deposition. Analyses of grainsize distribution were coupled with further data on tephra texture and morphology, and numerical simulations. Several components were identified based either on purely textural or purely shape characteristics. Shape parameters related to the form of the grains (aspect ratio) are consistent across grainsizes and components. However, roughness parameters (solidity, convexity, concavity index) vary non-uniformly with particle size and componentry. Ash was formed through complex fragmentation of heterogenous magma, starting in the conduit, extending to the explosion jet, and resulting into a large variability of particle shapes, density and textures which distribute non-uniformly across grainsizes. This variability determines variable traveling potential within the volcanic plume and thus non uniform distribution in the deposit. Componentry variations along the dispersal axis suggest that density is the most effective parameter in controlling particle settling. However, extreme shapes, such as very elongated particles formed by surface tension instabilities in the jet, have the largest potential of being transported in the plume and can disperse downwind up to tens of km. Our results suggest that heterogeneities in textures and morphologies of particles are fundamental characteristics of tephra from frequently erupting volcanoes and should be accounted for plume dispersal modelling and hazard assessment.